Experimental Investigations for Use of ABS Replicas in Investment Casting Applications - Singh, Rupinder; Gupta, Munish K. (Asian Review of Mechanical Engineering, 2013)
In the present research work effort has been made to study the use of acrylonitrile butadiene styrene (ABS) replicas in investment casting (IC) applications. The study starts with selection of the component for industrial application with an idea of improvement in dimensional accuracy (Δd) of the component. The input parameters are part orientation in fused deposition modeling (FDM), number of layers, layer combination and type of materials in IC. The study highlights the percentage contribution of different input parameters on Δd for ABS replicas in IC.